Reboot - Sriramesh, Krishnamurthy (knjige, 2022)
The pandemic has demonstrated the fragility of humans and the societies we inhabit. Personal relationships were suspended and digitalized. Atomized employees were asked to work from home, and the very definition of the workplace seems to have been redefined. So, it is appropriate to ask whether organizations should be proactive and rediscover effective communication strategies and techniques. Is it time to explore the definition and distinction between what are internal and what are external relationships? Communication and public relations (in all its denominations: communication management, corporate communication, strategic communication…) have gained a new and bigger role in management around the world.
Keywords: Krizni management; Mednarodna posvetovanja; Odnosi z javnostmi; Poslovno komuniciranje